Inexpensive colloidal SnSb nanoalloys as efficient anode materials for lithium- and sodium-ion batteries. Issue 18 (8th April 2016) - Walter, Marc; Doswald, Simon; Kovalenko, Maksym V.
Abstract : The quest for higher energy densities of lithium-ion batteries (LIBs) and emerging sodium-ion analogues (SIBs) has motivated an intense research effort toward novel electrode materials. Abstract : The quest for higher energy densities of lithium-ion batteries (LIBs) and emerging sodium-ion analogues (SIBs) has motivated an intense research effort toward novel electrode materials. We report a simple and inexpensive colloidal synthesis of SnSb nanocrystals (NCs) and demonstrate their utility as lithium- and sodium-ion anode materials. In particular, SnSb NC Li-ion anodes deliver capacities of ∼890 mA h g −1 for 100 cycles at a current density of 200 mA g −1 and show excellent rate capability, reaching 90% and 80% of the theoretical capacity at current densities of 1000 and 5000 mA g −1, respectively. Similarly, SnSb NCs show also outstanding Na-ion storage properties with only ∼5% capacity loss over 100 cycles at a rate of 5000 mA g −1 . Full-cells can be constructed with SnSb anodes and state-of-the-art cathodes, achieving anodic capacities of 600 and 400 mA h g −1 with an average discharge voltage of 3.0 and 2.7 V for lithium- and sodium-ions, respectively.